A semi-automatic system for labelling seafood products and obtaining fishery management data: A case study of the bottom trawl fishery in the central Mediterranean Sea - Gioacchino Bono; Salvatore Cusumano, Cinzia Badalucco, Vito Pipitone; Sergio Vitale (Advances in Aquaculture and Fisheries Management, 2023)
This study is on the implementation of a semi-automatic labelling system (LS) of the Mediterranean Sea seafood harvest to address the increased need for seafood authentication and inherent difficulties of commonly used indirect techniques for estimating fisheries yield and fishing effort. Sensitive data required for anti-counterfeit policies, such as date and catch area, can be acquired and recorded on the label by userfriendly automated software that excludes any possible manipulation by the crew. Based on results obtained from the installation of the LS on bottom commercial trawlers, the system certified the origin of the seafood products and simultaneously provided, indirectly, geospatial fisheries yield and fishing effort data of the main exploited species.